Alveolar Distraction Osteogenesis The ArchWise Appliance and Technique - Erverdi, Nejat; Motro, Melih; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
The second edition of this comprehensive book describes a new alveolar distraction osteogenesis method that offers important advantages and can be used for the treatment of various orthopedic abnormalities and congenital malformations. Detailed guidance is provided on the selection of suitable candidates for alveolar distraction, including those with cleft lip and palate, with severe bone defects, skeletal class II malocclusions and cystic lesions involving the alveolus. All aspects of treatment using the ArchWise distraction appliance are then covered, including technical preparation, surgical set-up and osteotomies, docking site surgery, orthodontic finishing, implant placement and prosthetic restorations. Detailed information on the principles of distraction osteogenesis, bone histology and molecular interactions during the procedure is also provided. The book concludes with helpful case presentations covering different scenarios in which treatment with alveolar distraction osteogenesis is advisable. Given the nature of its content, the book will be of interest to all oral and maxillofacial surgeons, orthodontists and restorative dentists.
Keywords: Oral surgery; Maxillofacial surgery; Dentistry; Oral and Maxillofacial Surgery; Dentistry